Seasonal variation in skin temperature, blood flow and physiological functions in Zebu (Bos Indicus) and Karan Fries (Tharparkar X Holstein Friesian) cattle - Singh, S V; Devi, Rajni; Kumar, Yogendra; Choudhary, Renuka; upadhyay, R C (Indian Journal of Dairy Science, 2017)
The changes in skin temperature, blood flow and physiological functions of cattle were monitored during winter (THI=60) and summer (THI=83) seasons in zebu and Karan Fries cattle. Six each of Sahiwal, Tharparkar and Karan-Fries heifers of 18-24 months were selected from Livestock Research Centre of ICAR-NDRI, Karnal. The mean rectal temperature, respiration rate, pulse rate and blood pressure were higher during summer than winter in different cattle breeds. The rectal temperature, respiration rate and pulse rate of Sahiwal, Tharparkar and Karan-Fries cattle differed significantly during summer and winter. The diastolic and systolic blood pressure were also differed significantly (p=0.001) in all the breeds during both the seasons. Skin blood flow was significantly higher at dorsal, abdominal and middle ear part of body in zebu (Sahiwal, Tharparkar) than crossbred (Karan-Fries) cattle during summer and winter seasons. The skin blood flow showed positive correlation with skin temperature of different body parts and was significantly higher during summer than winter. Results of the present study clearly showed the differences among different parameters among the zebu and crossbred cattle and indicating the better adaptability of zebu compared to crossbred cattle during heat stress